2019
DOI: 10.18203/2320-1770.ijrcog20190275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical versus ultrasonographic fetal weight estimation and its correlation with actual birth weight

Abstract: Background: This is a prospective study was conducted at Obstetrics and Gynecology department, tertiary care Hospital, to compare the accuracy of clinical and ultrasonographic estimation of fetal weight at term with actual birth weight.Methods: The present study is a prospective comparative study of fetal weight estimation in Antenatal women with term gestation (37week to 42week of gestation) singleton pregnancy with vertex presentation, who had gestational age confirmed by dates and ultrasound scanning of<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The present study results showed that ultrasound results were not significantly different with actual birth weight, but Johnson's and Insler's formulas were significantly different with actual birth weight. Ultrasonography is as accurate as clinical methods in fetal weight estimation, which is consistent with some studies [30,31].…”
Section: Discussionsupporting
confidence: 90%
“…The present study results showed that ultrasound results were not significantly different with actual birth weight, but Johnson's and Insler's formulas were significantly different with actual birth weight. Ultrasonography is as accurate as clinical methods in fetal weight estimation, which is consistent with some studies [30,31].…”
Section: Discussionsupporting
confidence: 90%
“…These nonstandard measurements do not improve the effectiveness of sonography to predict birth weight, except in rare cases such as diabetic mothers. 11 The anterior placenta, maternal obesity, and oligohydramnios are all technical restrictions for sonographic fetal weight estimates. Other downsides of ultrasonography include its complexity and labor-intensive nature, as well as its limited view of fetal components.…”
Section: Discussionmentioning
confidence: 99%
“…In routine obstetric practice, clinical examination is done by measuring the symphysio-fundal height at each antenatal visit similar to a study done by Ingale A et al 11 In this work, we compared clinical and sonographic methods of predicting fetal weight prospectively at term and found that clinical appears to be as accurate as ultrasonographic approaches, which is similar to the findings of Dare et al, Avirupa Guha Roy et al, 12 and Ingale A et al 11 Ultrasonography has become the recognised method for estimating fetal weight in most centres. Johnson's and Dawn's formulas for estimating clinical birth weight are now obsolete.…”
Section: Discussionmentioning
confidence: 99%